Examination of critical factors influencing ruminant disease dynamics in the Black Sea Basin - Arede, Margarida; Beltrán-Alcrudo, Daniel; Aliyev, Jeyhun; Chaligava, Tengiz; Keskin, Ipek; Markosyan, Tigran; Morozov, Dmitry; Oste, Sarah; Pavlenko, Andrii; Ponea, Mihai; Starciuc, Nicolae; Zdravkova, Anna; et al. (Frontiers in Veterinary Science, 2023)
Ruminant production in the Black Sea basin (BSB) is critical for national economies and the subsistence of rural populations. Yet, zoonoses and transboundary animal diseases (TADs) are limiting and threatening the sector. To gain a more comprehensive understanding, this study characterizes key aspects of the ruminant sector in nine countries of the BSB, including Armenia, Azerbaijan, Belarus, Bulgaria, Georgia, Moldova, Romania, Türkiye, and Ukraine. We selected six priority ruminant diseases (anthrax, brucellosis, Crimean Congo haemorrhagic fever (CCHF), foot-and-mouth disease (FMD), lumpy skin disease (LSD), and peste des petits ruminants (PPR)) that are present or threaten to emerge in the region. Standardized questionnaires were completed by a network of focal points and supplemented with external sources. We examined country and ruminant-specific data such as demographics, economic importance, and value chains in each country. For disease-specific data, we analysed the sanitary status, management strategies, and spatial and temporal trends of the selected diseases. The shift from a centrally planned to a market economy, following the collapse of the Soviet Union, restructured the ruminant sector. This sector played a critical role in rural livelihoods within the BSB. Yet, it faced significant challenges including pastoralism low sustainability, technological limitations, unregistered farms, and informal animal trade due to economic factors and insufficient support for formal trade development. Additionally, socio-cultural drivers such as traditional production practices, and cultural-religious events also played a role. In the Caucasus and Türkiye, where diseases were present, better ruminant health was driven by access to trading opportunities. Conversely, European countries, mostly disease-free, prioritized preventing disease incursion to avoid a high economic burden. While international initiatives for disease management are underway in the BSB, there is still a need for stronger international partnerships and resources to strengthen veterinary health capacity, protect animal health and improve ruminant production.